An effective Meta-Heuristic Algoritm for solve multicriteria job Jhop Scheluding problem with maintenance activitie, ISSN/ISBN 2040-7459/1479-4861 - Bahmani Younes; Smadi Hacene; Benzouai Mzssaoud (RJSAET.Research Journal of Applied Sciences Engineering and technology, 2015)
In this study, a metaheuristic based on the Non-dominated Sorting Genetic Algorithm type II (NSGA-II) is proposed to solve the Multi-Criterions Job Shop Scheduling Problem (MCJSSP) under resources availability constraints. Availability periods and starting time of maintenance activities are supposed to be flexible. The MCJSSP requires, simultaneous minimization several antagonistic criteria, such as the maximum completion time of all jobs (Makespan), production cost and maintenance cost. To validate the proposed approach we tested it on forty-four instances references. The results show that our approach is experimentally promising to solve practical problems.